THE BUILDING AND IMPLANTATION OF NATIONAL POLITICS FOR INTEGRATIVE AND COMPLEMENTARY PRACTICES IN THE UNIQUE HEALTH SYSTEM AND THE MEDICINAL PLANTS’ AND PHYTOTHERAPICS’ NATIONAL POLITICS. - Souza, Barcelos de (Revista de Ciências Agroveterinárias, 2006)
Interview with Dr. Ângelo Giovani Rodrigues.